Mapping the Tura-Masara Limestone Quarries - Harrell, James A..
The Tura-Masara limestone quarries, near Cairo, supplied stone to the Old and Middle Kingdom pyramid complexes of the Memphite necropolis and also for many temples of the Middle Kingdom and later at sites throughout the Nile Valley and Delta. These underground quarries, commonly referred to as galleries, were previously known primarily from their many inscriptions. Maps with detailed plans of about 70 of the galleries were recently discovered in the British Library. These were prepared at the beginning of the Second World War for the British military in order to facilitate its occupation of the bomb-proof galleries. The maps, which also report the surface area of each gallery, not only provide much-needed cartographical documentation of one of ancient Egypt’s most important quarry complexes but also new insights into the quarrying process and use of the Tura-Masara limestone.